Production and Analysis of Golean as Alternative Tea - Jimenez, Nelia G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study developed and evaluated GOLEAN Alternative Tea, made from Bottle Gourd skin, Lemongrass leaves, and Anonang leaves as an alternative herbal beverage. Using descriptive and experimental research design, 90 respondents, composed of 30 tea consumers, 30 tea makers, and 30 tea sellers, assessed its acceptability and marketability in Marikina City during the School Year 2024-2025. The tea exhibited low moisture content (12.0 g/100g), a pH of 6.04, minimal vitamin C (<1 mg/100g), and acceptable microbial levels (1.2 × 10² CFU/g). Assessments were conducted using the Nine-Point Hedonic Rating Scale for acceptability and the Five-Point Likert Scale for marketability. Statistical analysis was performed using Weighted Mean and One-way ANOVA. Findings revealed that consumer respondents rated the tea as “Extremely Acceptable” (EA) with scores of 8.54, 8.60, and 8.51 for proportions A, B, and C, respectively. Significant differences in taste perception were observed among the groups, while no significant differences were found in marketability evaluations. The marketability ratings indicated that proportions A (4.76), B (4.79), and C (4.79) were deemed “Very Highly Marketable.” In conclusion, the study confirms the viability of GOLEAN Alternative Tea as a natural and affordable herbal beverage, highlighting its potential for high acceptability and marketability while addressing challenges and offering recommendations for improvement based on respondent feedback.